Monetary asymmetries without (and with) price stickiness - Ivan Jaccard (European Central Bank (ECB), 2024)
The evidence suggests that monetary policy transmission is asymmetric over the business cycle. Interacting financing frictions with a preference for liquidity provides an explanation for this fact. Our mechanism generates monetary asymmetries in a model that jointly reproduces a set of asset market and business cycle facts. Accounting for the joint dynamics of asset prices and business cycle fluctuations is key; in a variant of the model that is unable to produce realistic macro-finance implications, monetary asymmetries disappear. Our results suggest that asymmetries in the transmission mechanism critically depend on the macro-finance implications of monetary policy models, and that resorting to nonlinear techniques is not sufficient to detect monetary asymmetries.
Keywords: E31; E44; E58; 330; Money Demand; Nonlinear Solution Methods; Asset Pricing in DSGE Models; Term Premium; Stochastic Discount Factor